The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19148810
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Health Care Access during the COVID-19 Pandemic: Estimates of National Japanese Data, June 2020–October 2021

Abstract: The COVID-19 pandemic has disrupted health care access around the world, both for inpatients and outpatients. We applied a quasi-Poisson regression to national, monthly data on the number of outpatients, number of inpatients, length of average hospital stay, and the number of new hospitalizations from March 2015 to October 2021 to assess how these outcomes changed between June 2020 to October 2021. The number of outpatient visits were lower-than-predicted during the early phases of the pandemic but normalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In addition, many patients may have been reluctant to seek care in hospitals for fear of contracting COVID-19 infection . As a result, a prior study reported a decrease in the number of outpatient visits after the declaration of the national state of emergency . Thus, many patients with COVID-19-like symptoms stayed home without undergoing PCR testing or accessing primary care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many patients may have been reluctant to seek care in hospitals for fear of contracting COVID-19 infection . As a result, a prior study reported a decrease in the number of outpatient visits after the declaration of the national state of emergency . Thus, many patients with COVID-19-like symptoms stayed home without undergoing PCR testing or accessing primary care.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 As a result, a prior study reported a decrease in the number of outpatient visits after the declaration of the national state of emergency. 29 Thus, many patients with COVID-19-like symptoms stayed home without undergoing PCR testing or accessing primary care.…”
Section: Jama Network Open | Health Policymentioning
confidence: 99%
“…particularly in the early stages of the pandemic. (Makiyama et al, 2021;Tanoue et al, 2022) Although telemedicine was temporarily permitted, reduced opportunities for face-to-face medical care triggered reduced opportunities for both verbal and nonverbal medical communication.…”
Section: Discussionmentioning
confidence: 99%
“…Japan was no exception, with the number of non-COVID-19-infected patients visiting hospitals decreasing significantly because of the state of emergency declared and outdoor restrictions imposed as soon as the wave of infection began in March 2020. 2 Because of postponing or canceling of scheduled surgeries, most of the oncological surgeries, including low anterior resection (LAR) for rectal cancer, temporarily decreased. 3 The impact of COVID-19 was not only a change in the number of surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Policies were made and strongly implemented in each country to prevent contagion, resulting in a significant impact on overall health care. Japan was no exception, with the number of non–COVID‐19‐infected patients visiting hospitals decreasing significantly because of the state of emergency declared and outdoor restrictions imposed as soon as the wave of infection began in March 2020 2 . Because of postponing or canceling of scheduled surgeries, most of the oncological surgeries, including low anterior resection (LAR) for rectal cancer, temporarily decreased 3 …”
Section: Introductionmentioning
confidence: 99%